Chemical Constituents of Essential Oil of the Leaves of Eryngium foetidum from Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2008)
The essential oil of leaves of Eryngium foetidum from Bangladesh was analyzed by GC-MS. Sixty three compounds have been identified with (E)-2-dodecenal (37.4 %), dodecanoic acid (10.7 %), trans-2-dodecanoic acid (9.7 %), (E)-2-tridecenal, (6.7 %), duraldehyde (5.1 %) and tetradecanal (4.4 %) as the major constituents. Bangladesh J. Sci. Ind. Res. 42(3), 347-352, 2007